Pengaruh Literasi Digital Konten Iklan Tiktok Terhadap Perilaku Konsumtif Gen-Z Di Jakarta Utara - Danang Ridho Pratomo; Yan Bastian (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The massive growth of social commerce has transformed the lifestyle landscape of urban communities. This explanatory quantitative study aims to examine the influence of digital literacy regarding TikTok advertising content on the consumptive behavior of Generation Z in North Jakarta, grounded in the Stimulus-Response (S-R) theory framework. Primary data were collected via online questionnaires distributed to 100 active TikTok users selected through purposive sampling. Data analysis was subsequently conducted using the simple linear regression method with IBM SPSS software. Hypothesis testing results (partial t-test) yielded a calculated t-value of -1.651 with a significance level of 0.102 (> 0.05), indicating that the null hypothesis (H0) was accepted and the alternative hypothesis (H1) was rejected. These findings empirically demonstrate that there is no significant influence of digital literacy regarding TikTok advertising content on consumptive behavior. Based on the coefficient of determination (R²) analysis, the independent variable contributed only 2.7%, while the remaining 97.3% was influenced by external factors outside the model. This paradox suggests that while urban Gen Z possesses a high level of digital literacy, this understanding merely fosters critical awareness of advertisements without effectively curbing impulsive purchasing—behaviors likely driven by psychosocial factors beyond the scope of this study, such as Fear of Missing Out (FOMO), social validation, urban lifestyle pressures, and the convenience of fintech features..